Differentiating Probiotics and Prebiotics in Terms of Mechanism of Action and Clinical Application - Jankowska, Marlena; Baran , Karolina; Jańczyk , Natalia; Bartnik , Katarzyna; Pokrzepa , Jakub; Presak , Michał; Pacołta , Adrianna; Nalepka , Marcelina; Pograniczny , Mikołaj; Mielżyńska , Adrianna (Quality in Sport, 2025)
This systematic review explores the key differences between probiotics and prebiotics in terms of their mechanisms of action and clinical applications. Probiotics are live microorganisms that confer health benefits when consumed in adequate amounts, whereas prebiotics are non-digestible food ingredients that promote the growth of beneficial gut bacteria. The review highlights how these two categories of microbiota-targeted interventions work independently and synergistically to maintain and improve human health. A detailed examination of their impact on gastrointestinal health, metabolic disorders, immune function, neurological health, and more is provided. The clinical efficacy of specific probiotic strains and prebiotic compounds is also evaluated. This comprehensive overview aims to inform both clinical practice and future research on microbiota modulation strategies.